Dynamics of self-assembled cytosine nucleobases on graphene. (13th March 2018) - Saikia, Nabanita; Johnson, Floyd; Waters, Kevin; Pandey, Ravindra
Abstract: Molecular self-assembly of cytosine (C n ) bases on graphene was investigated using molecular dynamics methods. For free-standing C n bases, simulation conditions (gas versus aqueous) determine the nature of self-assembly; the bases prefer to aggregate in the gas phase and are stabilized by intermolecular H-bonds, while in the aqueous phase, the water molecules disrupt base–base interactions, which facilitate the formation of π -stacked domains. The substrate-induced effects, on the other hand, find the polarity and donor–acceptor sites of the bases to govern the assembly process. For example, in the gas phase, the assembly of C n bases on graphene displays short-range ordered linear arrays stabilized by the intermolecular H-bonds. In the aqueous phase, however, there are two distinct configurations for the C n bases assembly on graphene. For the first case corresponding to low surface coverage, the bases are dispersed on graphene and are isolated. The second configuration archetype is disordered linear arrays assembled with medium and high surface coverage. The simulation results establish the role of H-bonding, vdW π -stacking, and the influence of graphene surface towards the self-assembly. The ability to regulate the assembly into well-defined patterns can aid in the design of self-assembled nanostructures for the next-generation DNA based biosensors and nanoelectronic devices.